PERSEPSI SISWA TERHADAP PENGGUNAAN VIDEO ANIMASI BERBASIS DORATOON - Ni Made Gangga Adnya Ari Kemuda; I Gede Bayu Kartika Yasa (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
Blended learning has become a learning adaptation in the post-COVID-19 pandemic era. This means that schools have implemented offline learning in the classroom but the essence of online learning is still available, such as using audiovisual media in learning. This research aims to determine the fifth-grade students' perceptions of the use of Doratoon-based animated videos in Civic Education learning. This research used mixed research methods which consisted of a questionnaire for fifth-grade students and in-depth interviews with 5 students among the survey respondents. The results explained that fifth-grade students tend to strongly agree with the use of animated videos as learning media in Civic Education class. This was proven by the mean score of 4,5 in the survey which showed that students strongly agree with the implementation of Doratoon-based animation videos in the aspects of students' interest in Doratoon animation videos, ease of understanding, and ease of absorbing more information. This research is expected to help teachers determine effective learning media for teaching fifth-grade students in Civic Education subjects.